Analisis Yuridis Bentuk Penyelesaian Sengketa Tanah Melalui Mediasi dan Arbitase - Maulaya, Muhammad Zulfa; Pradana, Aditya Fani; Umam, Muhammad Choerul; Widyastuti, Tiyas Vika; Wildan, Muhammad (Indonesian Journal Publisher, 2024)
The aim of this article is to describe the form of land rescue resolution using normative juridical analysis techniques. Settlements and land-related cases are usually settled through the official legal system and the applicable courts. There are some studies on the settlement of land disputes in Indonesia. This research uses a qualitative descriptive method, namely explaining the phenomenon or relationship of a problem in text form. The data source for this research is obtained through primary and secondary data. Primary data from this research uses legal materials consisting of: 1) the 1945 Constitution; 2) the Civil Code; and 3) Law No. 30 of 1999 regarding arbitration and settlement. The results of this research show that the form of land dispute resolution through arbitration and mediation is very appropriate to use, considering that the costs are not expensive and do not cause losses to the parties in the dispute. Mediation is a dispute settlement process involving third parties as intermediaries to help the parties reach an agreement. Mediation has been used in the settlement of land disputes in various areas of Indonesia, such as Kelurahan Mauliru District of East Sumba and Yogyakarta City. Mediation and arbitration are also methods of dispute resolution involving neutral third parties. The application of mediation and arbitration in the settlement of land disputes is expected to bring about justice and legal certainty.